2021
DOI: 10.1109/access.2021.3081395
|View full text |Cite
|
Sign up to set email alerts
|

Multiobjective Optimization of Photo Voltaic Battery System Sizing for Grid-Connected Residential Prosumers Under Time-of-Use Tariff Structures

Abstract: The integration of photovoltaic and battery energy storage systems into utility grids is favorable for electricity customers, especially for high consumption load patterns due to the high electricity bill. To increase the annual bill savings and decrease the dependency on the utility grid, a procedure of optimally sizing the PV battery system is presented in this paper. A MATLAB-based code of the genetic algorithm is used to maximize the system self-sufficiency and minimize the discounted payback period while … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…S/./month (0.215 $/kWh). The grid sellback price is not regulated yet in Peru, although it can be set based on the particular characteristics of each country's electrical grid (Fraunhofer, 2021;Gabr et al, 2021). For the purpose of this work, the price is considered as 30% of the grid power, i.e.…”
Section: Energy Cost Of the Case Studiesmentioning
confidence: 99%
“…S/./month (0.215 $/kWh). The grid sellback price is not regulated yet in Peru, although it can be set based on the particular characteristics of each country's electrical grid (Fraunhofer, 2021;Gabr et al, 2021). For the purpose of this work, the price is considered as 30% of the grid power, i.e.…”
Section: Energy Cost Of the Case Studiesmentioning
confidence: 99%
“…The initial investment cost is mainly the purchase cost of related equipment during the construction of the power supply structure of the base station. To calculate the net present value cost during the whole life cycle, the impact of the discount rate should be considered [36]. The initial investment cost calculation is shown in Equation (11).…”
Section: Initial Investment Costmentioning
confidence: 99%
“…With variable energy prices in the grid (dynamic tariffs), it is also possible to implement price arbitrage and aim to minimize the energy consumed from the grid, as further discussed in [22][23][24][25][26]. Based on the presented figure, it can be concluded that in order to effectively use the energy available from a renewable source, it must be stored.…”
mentioning
confidence: 99%
“…• With variable energy prices in the grid (dynamic tariffs), it is also possible to implement price arbitrage and aim to minimize the energy consumed from the grid, as further discussed in [22][23][24][25][26]. Due to the number of possible operating modes and scenarios and the possibility of providing additional demand-side response (DSR) services to the grid operator, the complexity of such a system is high and requires the use of a supervisory control system.…”
mentioning
confidence: 99%